2022
DOI: 10.1111/medu.14802
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in assessment: How useful is it?

Abstract: The author unveils a strategy for enquiry that can facilitate identification of best practices for involving real patients in OSCE and WBA competency‐based assessments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Mystery shopping has been used to investigate prescribing and pharmaceutical sales provisions (Björnsdottir et al, 2020 ; Cheo et al, 2020 ; Collins et al, 2020 ); but not student competencies. Generally, real life patients are used in WBAs (Khalife et al, 2022 ; Malau-Aduli, 2022 ) but we needed to compare performance with the same cases so we trained simulated patients to be used. Due to time constraints and mystery shopper and workplace supervisor availability, it was not possible to visit all the students within their placement period but 92/289 students is a reasonable representation of the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mystery shopping has been used to investigate prescribing and pharmaceutical sales provisions (Björnsdottir et al, 2020 ; Cheo et al, 2020 ; Collins et al, 2020 ); but not student competencies. Generally, real life patients are used in WBAs (Khalife et al, 2022 ; Malau-Aduli, 2022 ) but we needed to compare performance with the same cases so we trained simulated patients to be used. Due to time constraints and mystery shopper and workplace supervisor availability, it was not possible to visit all the students within their placement period but 92/289 students is a reasonable representation of the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…WBAs and OSCEs are both widely used for the assessment of clinical competence in health education, however, there has not been any literature comparing the two contexts and how students perform in a simulated versus un-simulated environment. Real life patients are commonly used in WBAs to assess competencies in the workplace (Khalife et al, 2022 ), and have found to be useful to have an authentic voice and provide more valuable feedback that prepare students for practice (Malau-Aduli, 2022 ). Our WBA used simulated patients as mystery shoppers as our study aims to compare the same clinical case in OSCEs and WBAs.…”
Section: Introductionmentioning
confidence: 99%